Solid-state synthesis of cubic ZnTe nanocrystals using a microwave plasma - Tawat Suriwong (2018)
Cubic ZnTe nanocrystals were produced from 1:1 and 1.8:1 molar ratios of Zn:Te by a 900 W microwave plasma. The phase was detected using X-ray diffraction (XRD), which are in accordance with those of the simulations, and selected area electron diffraction (SAED). Raman spectroscopy, scanning electron microscopy (SEM) and transmission electron microscopy (TEM) showed that the products were nanocrystals with different orientations, including three longitudinal optical (LO) vibrations at 205, 410 and 620 cm- 1and a transverse optical (TO) vibration at 166 cm- 1. Their green emissions were detected at 562 nm (2.21 eV) using luminescence spectrophotometry. © 2009 Elsevier B.V. All rights reserved.